2014
DOI: 10.1186/2040-2392-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rare DNA sequence variants in high-risk autism families and their prevalence in a large case/control population

Abstract: BackgroundGenetics clearly plays a major role in the etiology of autism spectrum disorders (ASDs), but studies to date are only beginning to characterize the causal genetic variants responsible. Until recently, studies using multiple extended multi-generation families to identify ASD risk genes had not been undertaken.MethodsWe identified haplotypes shared among individuals with ASDs in large multiplex families, followed by targeted DNA capture and sequencing to identify potential causal variants. We also assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 85 publications
1
33
0
1
Order By: Relevance
“…These findings are consistent with other studies that have also identified multiple genetic etiologies among affected individuals within multiplex ASD pedigrees. For example, Shi et al (2013) identified a number of potentially deleterious rare single-nucleotide variants shared between cases in a two generational multiplex family, and Matsunami et al (2014) identified a complex pattern of segregating SNVs and CNVs in multigenerational ASD pedigrees: crucially, several pedigrees segregated more than one detrimental sequence variant, and among these pedigrees CNVs of potential etiological significance to ASD were also observed. Clearly, therefore, and as demonstrated in our own study, the genetic etiology of ASD in such families is likely complex and not necessarily involving the same genetic mechanisms across closely related cases.…”
Section: Discussionmentioning
confidence: 95%
“…These findings are consistent with other studies that have also identified multiple genetic etiologies among affected individuals within multiplex ASD pedigrees. For example, Shi et al (2013) identified a number of potentially deleterious rare single-nucleotide variants shared between cases in a two generational multiplex family, and Matsunami et al (2014) identified a complex pattern of segregating SNVs and CNVs in multigenerational ASD pedigrees: crucially, several pedigrees segregated more than one detrimental sequence variant, and among these pedigrees CNVs of potential etiological significance to ASD were also observed. Clearly, therefore, and as demonstrated in our own study, the genetic etiology of ASD in such families is likely complex and not necessarily involving the same genetic mechanisms across closely related cases.…”
Section: Discussionmentioning
confidence: 95%
“…We report here on over four years of clinical experience with a real-world referral base for testing on an ultra-high resolution chromosomal microarray specifically designed to extend the scope of detection for individuals with ASD and other neurodevelopmental disorders. This microarray was optimized through the addition of probes targeting genomic regions more recently identified to have pathogenic relevance for DD, ID, and ASD [21,35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…However, Matsunami et al (2014) asserted that no single inheritance model for ASD could be correct, because many varied forms of genetic transmission occur with ASD, and Ronemus et al (2014) noted that ASD genetic transmission recurrence risk must vary for families with one child with ASD (simplex) and families with more than one child with ASD (multiplex). An example of varied genetic transmission was reported by Jiang et al (2013), who found multiple varied ASD inheritance patterns in just 16 families: 12 rare X-linked deleterious variants, 7 rare deleterious autosomal-dominant mutations, 13 deleterious missense mutations, and 15 de novo deleterious mutations.…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%